2012
DOI: 10.1118/1.4752422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiation induced current on the quality of MR images in an integrated linac‐MR system

Abstract: The presence of RIC in MR RF coils leads to a loss of SNR which is directly related to the linac dose rate. The RIC related loss in SNR is likely to increase for systems that are able to provide larger than 250 MU∕min dose. Some of this SNR loss can be recovered through the use of a postprocessing algorithm, which removes the RIC artefact from the image k-space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
2
22
1
Order By: Relevance
“…[12][13][14][15] Radiofrequency interference between the MRI and Linac has also been studied. 16,17 The various dosimetry changes caused by the magnetic fields are also described, including both transverse [18][19][20][21][22][23][24][25][26][27] and longitudinal magnetic fields. 22,[28][29][30] The performance of common radiation detectors in magnetic fields has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Radiofrequency interference between the MRI and Linac has also been studied. 16,17 The various dosimetry changes caused by the magnetic fields are also described, including both transverse [18][19][20][21][22][23][24][25][26][27] and longitudinal magnetic fields. 22,[28][29][30] The performance of common radiation detectors in magnetic fields has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding values for larger DSV were 6.32 ± 0.32 μT/√kW and 6.46 ± 0.39 μT/√kW at 40 cm and 50 cm respectively. interference described to date [6,8,9]. During dynamic image acquisition we were unable to detect any statistical difference in signal with the radiation beam turned on in any of the tests.…”
Section: Resultsmentioning
confidence: 65%
“…This is in contrast to previous studies which have either shown no observable effect 10 or described a reduction in SNR attributed as being caused by induction in the copper conductor directly. 11 Our results show a large increase in background intensity, which does not occur when the linear accelerator is in operation and the MLC is closed, thereby showing that it is not extraneous noise from the accelerator (which is outside a RF cage). The elevation of noise has the potential to reduce overall SNR within the image but this is highly dependent on the RF coil setup.…”
Section: Discussionmentioning
confidence: 61%